Beyond the Degree: A Reflective Practitioner Perspective on Management Education and Organizational Practice in Madhesh Province - Karn, Dipesh Kumar (Apex Journal of Business and Management, 2026)
Madhesh Province, Nepal’s agricultural hub bordering India, faces pressing needs for practice-oriented management education amid persistent theory-practice gaps in leadership, customer service, and finance. This reflective practitioner study examines alignment through insights from 127 professionals. To assess practitioners’ perceptions of management education-practice alignment in Madhesh Province; evaluate curricula, teaching methods, and experiential learning applicability; analyze variations by experience, role, and organization type; and reflect on gaps. Mixed-methods design combines quantitative survey (N=127; 5-point Likert scale via Google Forms; analyzed in SPSS v.25: descriptives, ANOVA) with qualitative reflections from the researcher’s Madhesh-based accounting/management experience. Non-probability convenience sampling suited the undefined population. Classroom methods rated moderately (M=3.35 case studies; M=3.21 applicability), but internships (M=2.17), industry exposure (M=2.72), and workplace confidence (M=2.54) scored low. Low reliability (α=0.125) signals multidimensional views; no experience differences (F=0.350, p=0.705). Reflections highlight deficiencies in accounting software, taxation, labor laws, and trade. Weak experiential learning demands industry partnerships and practitioner-led reforms to boost employability and regional growth.